Optimal design and operation of damping controllers in PV–wind integrated sustainable energy grids considering system uncertainties - Mohsen Darabian; Farkhondeh Jabari; Mohsen Ahmad Khani (IET Renewable Power Generation, 2023)
Abstract This paper aims to present an optimization method for the best bus selection (BBS) in the large‐scale power systems in order to send the input signals to the damping controllers. In this regard, a submodular function is first defined to calculate the distance between the unstable vectors of the system and the controllability Gramian leading to find a set of buses for installation of the damping controllers. Based on the results obtained from the BBS approach, the number of candidate buses will be increased to deal with the inter‐area oscillations by introducing an event‐triggered based auxiliary scheme. According to the candidate buses and the power system operating condition, the most critical buses of the candidate set is allowed to participate as the input signals of damping controllers to reduce the inter‐area oscillations. The proposed algorithm is implemented on an interconnected large power system in the presence of wind and solar farms. These renewable energy resources are connected to the power system through the multi‐terminal DC network, so that their power products can be damped and injected into the power grid by designing the damping controllers. The simulations have been analysed using MATLAB software under different scenarios.